Synthesis and characteristics of polyurethane acrylate gel polymer electrolyte for dye sensitized solar cell application - Chai, Kai Ling (2022)
Solid and liquid electrolytes pose opposing advantages and disadvantages. Solid electrolyte has lower electrochemical performance in terms of ionic conductivity but has wide operating temperatures. However, liquid electrolyte has greater electrochemical performance but they easily leak and corrode components that come into contact with it. Gel polymer electrolyte (GPE) aims to combine the advantages of both solid and liquid electrolyte in one single package. In this work, dye sensitized solar cells (DSSCs) was fabricated from polyurethane acrylate (PUA) GPE which have been enhanced with varying amounts of (i) tetrabutylammonium iodide (TBAI), (ii) TBAI and lithium iodide (LiI) and (iii) TBAI, LiI and 1-butyl-3-methylimidazolium ionic liquid (BMII). The PUA was characterised using wet chemical tests such as Oxirane Oxygen Content test, Acid value test, Hydroxyl value test and Iodine Value test. Furthermore, the PUA was characterised by FTIR (Fourier Transform Infrared spectroscopy) and EIS (Electrochemical Impedance Spectroscopy). With the FTIR spectrum, it proved that PUA was successfully synthesized by epoxidation, hydroxylation and introduction of isocyanate group processes. Based on the Nyquist plot of pure PUA, the ionic conductivity (σ) obtained was 5.60 × 10-6 S cm-1. The PUA polymer was enhanced with various iodide salts to increase its electrochemical performance. All GPE systems prepared were characterised using FTIR, thermal gravimetric analysis (TGA) and EIS. PUA were prepared with TBAI salt as the first GPE system. FTIR was performed to determine the formation of complexation between PUA and TBAI salt. It was observed that 30 wt. % TBAI salt (A3 electrolyte) shows the highest σ of 1.88×10-4 S cm-1 with the highest charge mobility (μ) of 6.24×10-7 cm2 V-1 s-1 and diffusion coefficient (D) of 1.60×10-8 cm2 s-1 which estimated from fitting the Nyquist plots. The A3 electrolyte recorded the highest solar conversion efficiency (η) of 1.97 %. The highest η was due to low charge transfer resistance (Rpt) of 2.54 Ω at the electrolyte/counter electrode interface along with low charge transfer resistance (Rct) of 24.97 Ω at TiO2/dye/electrolyte interface and the charge diffusion resistance (Rd) of 34.14 Ω in the redox electrolyte. This A3 electrolyte was then further enhanced with the addition of LiI and was observed that 5.00 wt. % LiI (B2 electrolyte) shows the best result. B2 electrolyte shows the maximum σ of 2.34×10-4 S cm-1. This was because B2 electrolyte had the highest μ of 1.65×10- 6 cm2 V-1 s-1 and D of 4.25×10-8 cm2 s-1. B2 electrolyte indicated the highest η of 5.09 % due to low value of Rpt, Rct and Rd. B2 electrolyte then further enhanced with the addition of BMII ionic liquid and 6 wt. % BMII (C3 electrolyte) shows the best result. The C3 electrolyte manages to achieve an ionic conductivity value of 4.17 ×10-4 Scm-1 with highest μ of 2.03×10-6 cm2 V-1 s-1 and D of 5.20×10-8 cm2 s-1. 5.72 % of η obtained with low Rpt, Rct and Rd. This work shows that PUAbased electrolytes have the potential for DSSC applications.